2013
DOI: 10.1002/j.1552-4833.2013.35918.x
|View full text |Cite
|
Sign up to set email alerts
|

Oculo-Auriculo-Vertebral Spectrum, Cat Eye, and Distal 22q11 Microdeletion Syndromes: A Unique Double Rearrangement

Abstract: An array‐CGH on 19‐year‐old male showed a proximal 1.11 Mb duplication and a distal 1.7 Mb deletion of 22q11.2 regions flanking the Velocardiofacial/DiGeorge syndrome region that remained intact. FISH analyses revealed both abnormalities to be on the same homolog 22. This double rearrangement lead to the co‐existence of two syndromes: Cat eye and distal 22q11.2 microdeletion syndromes with a rare associated phenotype of oculo‐auriculo‐vertebral spectrum (OAVS). A review of the literature indicates that this is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Skeletal and soft tissue asymmetries of craniofacial structures, as well as dynamic facial asymmetries, have been observed in patients with genomic imbalances on the 22q11 region [28][29][30][31][32][33].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Skeletal and soft tissue asymmetries of craniofacial structures, as well as dynamic facial asymmetries, have been observed in patients with genomic imbalances on the 22q11 region [28][29][30][31][32][33].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Moreover, clinical studies have shown that, following careful history and clinical examination of the relatives of probands with OAVS, up to 45% of "unaffected" relatives do have minor OAVS manifestations [13]. Reports of familial cases following Mendelian inheritance [4,[14][15][16][17], as well as evidence for genetic linkage in two families [18,19], and the presence of OAVS features in patients with various chromosomal aberrations and genomic imbalances [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38], all suggest that some cases of OAVS have a genetic basis. Environmental causes have also been suggested, particularly twinning, assisted reproductive techniques and maternal pre-pregnancy diabetes [1,3].…”
Section: Introductionmentioning
confidence: 99%
“…Partially overlapping microduplications on 14q23.1 were identified in two families with autosomal dominant OAVS;46 47 one of these families included two first-degree relatives with clinical features of OAVS and Branchio-oto-renal syndrome; hence, the region 14q23.1 might harbour candidate genes for OAVS and additional first and second pharyngeal arch developmental disorders. Anomalies in 22q have been frequently documented in patients with OAVS, particularly the 22qter deletion,51 22q11.2 deletions,52–54 the 22q11.1-q11.21 (Cat-eye) region,56 57 and a partial 22 trisomy (47,XX,+der(22)t(11;22)(q23;q11)), which duplicates the 22q11 region 66. Chromosomal mosaicism for trisomy 2266 has also been described, making this region a good candidate for some cases of OAVS.…”
Section: Overview Of Oculo-auriculo-vertebral Spectrummentioning
confidence: 99%
“…The gene maps to human chromosome 22q11.2, and changes in this gene, due to either a point mutation or a deletion of part of chromosome 22 encompassing TBX1 , are considered to be responsible for many of the features of DiGeorge syndrome (DGS)/velocardiofacial syndrome (VCFS), a common congenital disorder characterized by neural‐crest‐related developmental defects. In the literature, 22q11.2 deletions have been also found to recur in patients with typical DGS/VCFS clinical features in association with hemifacial microsomia and microtia (Digilio et al., ; Dos Santos et al., ; Lafay‐Cousin et al., ; Spineli‐Silva, Bispo, Gil‐da‐Silva‐Lopes, & Vieira, ; Torti, Braddock, Bernreuter, & Batanian, ; Xu, Fan, & Siu, ), suggesting possible OAVS candidate genes in this segment. In view of these findings, TBX1 variant p.(Pro86Leu) likely represents the major determinant of the OAVS phenotype in the present patient, and the gene within 22q11.2 chromosome responsible for the OAVS features observed in patients with 22q11.2 deletion.…”
Section: Discussionmentioning
confidence: 99%